Strategi Akses Pasar Kerjasama Perdagangan Indonesia Kanada Dalam Kerangka Comprehensive Economic Partnership Agreeement (CEPA) - Choirulina, Eka; Paryadi, Deky (Cendekia Niaga, 2022)
Indonesia does not yet have a free trade agreement with Canada, as other ASEAN countries have done. Meanwhile, Indonesia-Canada trade activities have been running where Canada is Indonesia's export destination country at number 31 and companies from Canada have also opened businesses in Indonesia and employ Indonesian employees. For that, Indonesia considers Canada as one of the potential countries whose market can be developed. In this regard, Indonesia views the importance of Canada as a country that can be used as a trade partner bilaterally, so a strategy is needed in exploring international trade cooperation in a bilateral scheme. This study aims to analyze the strategy of Indonesia's trade and investment cooperation in Indonesia-Canada. This study is expected to answer the strategies that can be applied by negotiators in the Indonesia-Canada CEPA trade cooperation negotiations To answer the research aims, we use the SWOT method, where the formulation of a potential strategy for developing trade cooperation in the Indonesia-Canada CEPA (ICA-CEPA) is carried out through three stages, namely the input stage, the matching stage and the decision-making stage. Based on the results of the Internal and External Matrix and SWOT, Indonesia is in an S-O (Strength and Opportunity) position, which means that Indonesia must use its strengths to take advantage of Indonesia's opportunities in the Canadian market, both in the trade in goods and investment sectors. The trade cooperation explored should also include discussions of economic cooperation and increased capacity building in negotiations, so that the human resource factor that is Indonesia's strength can compete with partner countries.